An introduction to the poetics of sacred sound in twentieth-century music - Irlandini, Luigi Antonio (Revista Vórtex, 2013)
Along the twentieth century has occurred the beginning of a fusion between two very different horizons: Western musical composition and Hindu sonic theology. The essential content of this theology and the changes in Western musical language and aesthetics, society and culture which have allowed this fusion to take place are briefly outlined. Instrumental and vocal works by Karlheinz Stockhausen, Giacinto Scelsi, Michael Vetter and David Hykes provide specific examples and, in particular, raise the predicament between mysticism and rationalism, manifested in the dichotomy ècriture/inspiration. The study proceeds investigating the connections between music and meditation. In this context, overtone singing appears as a musical and meditative practice. The incorporation of this non-European or ancient vocal technique is evaluated as a dawning horizon in Western music. Overtone singing has required a practical emphasis through improvisation, suggesting a new musical praxis that does not separate composition from performance.